Reception hall used as a community space - Mumbai Archive Project (Jio Institute, 2024)
The reception hall is used as a community space and for meeting outside visitors. Up until the early 2000s, the feast day of St. Anthony, which falls on June 13th each year, was celebrated in the club with dance balls in the hall and dinners. Nowadays, it is a much quieter place, occasionally used by visitors for watching TV.